Media Literacy in Times of Crisis: First Results of the YO-MEDIA Project Handling the Voice of Educators, Teachers, and Journalists - Carenzio, Alessandra; Ferrari, Simona; Pasta, Stefano (Seminar.net, 2024)
The contemporary younger generation is facing a multitude of changes and adversities stemming from prevalent political, military, and pandemic crises that have garnered substantial attention in the media. In light of these circumstances, Media Literacy and critical thinking are paramount in navigating the influx of information and discerning veracity from misinformation. The rationale behind selecting this demographic as the focal point lies in the discernible trend wherein young individuals often peruse news content on their mobile devices with minimal contemplation, relying exclusively on social media platforms devoid of journalistic filtration. As delineated by various investigations, this juncture in their lives is pivotal to cultivating critical thinking skills. Such skills empower the youth to engage in autonomous thought processes, make informed decisions, and assess the repercussions of their actions. The contribution presents the outcomes of the interviews conducted in Italy, Spain, and Portugal within the project YO-MEDIA on Media Literacy in times of crisis, addressing the attention of educators, teachers, stakeholders, and journalists.